2023
DOI: 10.3390/s23041967
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone LiDAR Data: A Case Study for Numerisation of Indoor Buildings in Railway Stations

Abstract: The combination of LiDAR with other technologies for numerisation is increasingly applied in the field of building, design, and geoscience, as it often brings time and cost advantages in 3D data survey processes. In this paper, the reconstruction of 3D point cloud datasets is studied , through an experimental protocol evaluation of new LiDAR sensors on smartphones. To evaluate and analyse the 3D point cloud datasets, different experimental conditions are considered depending on the acquisition mode and the typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Another study [ 91 ] found that detecting buildings only by height differences may not be sufficient to resolve height ambiguity between buildings and trees. In addition, combining the high accuracy and density of LiDAR point clouds with the visual information from imagery has recently been shown to generate sophisticated and precise 3D building models [ 32 , 68 , 91 , 92 , 93 , 94 ]. Another study [ 92 ] integrated airborne LiDAR data and optical multi-view aerial imagery in two main steps (roof point segmentation and 3D roof model reconstruction), in which a 3D model of a building is reconstructed based on segmentations and 2D lines extracted from optical multi-view aerial photographs.…”
Section: Resultsmentioning
confidence: 99%
“…Another study [ 91 ] found that detecting buildings only by height differences may not be sufficient to resolve height ambiguity between buildings and trees. In addition, combining the high accuracy and density of LiDAR point clouds with the visual information from imagery has recently been shown to generate sophisticated and precise 3D building models [ 32 , 68 , 91 , 92 , 93 , 94 ]. Another study [ 92 ] integrated airborne LiDAR data and optical multi-view aerial imagery in two main steps (roof point segmentation and 3D roof model reconstruction), in which a 3D model of a building is reconstructed based on segmentations and 2D lines extracted from optical multi-view aerial photographs.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies relied on aerial, mobile or terrestrial LiDAR. However; handheld LiDAR sensors are getting popular as well, thanks to the advancement of technology that incorporated LiDAR sensors into smartphones (Catharia et al, 2023;Luetzenburg, Kroon, & Bjørk, 2021).…”
Section: Introductionmentioning
confidence: 99%